PERANAN PELABUHAN SUNGAI DUKU TERHADAP ARUS BARANG DAN JASA DI KOTA PEKANBARU - Marito, Riris; Isyandi, B.; Kornita, Sri Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in Pekanbaru Duku river port in 2016. The aim of this study was to determine the trend of the flow of goods and services as well as to determine whether the facility could increase the flow of goods and services in the Port River Duku Pekanbaru. The data used in this study are primary data and secondary data analysis method is quantitative descriptive analysis. In this study, the population is the entire passenger service users duku river port in the city of Pekanbaru in 2015. The number of samples taken is as much as 45 respondents was obtained by using the formula slovin. The survey results revealed that the trend of the flow of goods and services in ports river duku in 2016-2018 experienced a negative trend. And the condition of the main facilities and supporting facilities in ports river duku in both categories with a score of 3138 which is in the range from 1172-1532, but good facilities can not affect the increase of the flow of goods and services. Because more passengers switch to using ground transportation such as travel, in addition to low cost and passenger also be delivered directly to the address that will be addressed.Keywords : Duku River port, port facilities and flow of goods and services